2015
DOI: 10.1159/000373950
|View full text |Cite
|
Sign up to set email alerts
|

Early Secreted Antigen ESAT-6 of Mycobacterium Tuberculosis Promotes Apoptosis of Macrophages via Targeting the MicroRNA155-SOCS1 Interaction

Abstract: Background: The early secreted antigenic target 6-kDa protein (ESAT-6) of Mycobacterium tuberculosis (Mtb) not only acts as a key player for virulence but also exhibits a strong immunotherapeutic potential against Mtb. However, little is known about the molecular basis for its potential in immunotherapy. The present study was designed to unravel the role of miRNA-155 in ESAT-6-mediated enhancement of host immunity and apoptosis in macrophages. Methods: Lentivirus-mediated miR-155 sponge and miR-155 and SOCS1 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(53 citation statements)
references
References 32 publications
3
49
0
1
Order By: Relevance
“…Previous studies examining the role of miR-155 in regulating macrophage responses to mycobacteria in vitro have generated widely varying results. This discordance is likely due to the use of macrophage-like cell lines instead of primary macrophages, avirulent bacillus Calmette-Guérin instead of virulent Mtb, and widely differing in vitro experimental conditions (24)(25)(26)(27)(28). A recent study demonstrated that miR-155 −/− mice are more susceptible to Mtb infection during the late chronic stage of infection (18); however, the mechanism underlying this effect was not explored.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies examining the role of miR-155 in regulating macrophage responses to mycobacteria in vitro have generated widely varying results. This discordance is likely due to the use of macrophage-like cell lines instead of primary macrophages, avirulent bacillus Calmette-Guérin instead of virulent Mtb, and widely differing in vitro experimental conditions (24)(25)(26)(27)(28). A recent study demonstrated that miR-155 −/− mice are more susceptible to Mtb infection during the late chronic stage of infection (18); however, the mechanism underlying this effect was not explored.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the role of miRNAs in the regulation of the innate immune response, we characterized the transcriptional response of bone marrow-derived macrophages (BMMs) at 4,8,24, and 48 h following infection with Mtb and selected 3,473 differentially expressed genes based on the following criteria: Benjamini-Hochberg corrected Student's t test P value ≤ 0.05 and fold-change ≥ 2 (Fig. S1).…”
Section: Construction Of a Putative Mirna Regulatory Network In Macromentioning
confidence: 99%
See 1 more Smart Citation
“…Показано, что у человека измене-ние пути TLR2→miR-155→SOCS1 связано с формиро-ванием иммунного ответа с участием мононуклеарных клеток периферической крови [8]. У больных туберку-лезом белок ESAT-6 (early secreted antigenic target 6-kDa protein), продуцируемый Mycobacterium tuberculosis (Mtb) снижает иммунорективность, воздействуя на данный путь, что приводит к усилению апоптоза макрофагов [27].…”
Section: иммунологические реакции и Mir-155unclassified
“…Toll-like receptors(TLRs) have an essential role in the progress of innate immune responses [10-13]. In 2008, Burdelya et al reported that the agonist of TLR5 exerted strong radioprotective effects on mice [14].…”
Section: Introductionmentioning
confidence: 99%